Women Marketing Strategy for “Ramuan Sehat Jahe Merah” - T. D. Widajantie; D. Ratnawati; L. Romaisyah (Nusantara Science and Technology Proceedings)
Micro, Small and Medium Enterprises (MSMEs), which is a form of small business established by society, has contributed greatly to regional and national income. They also have a role in reducing the number of unemployed and improving the family economy. One example of MSMEs developed by the society is the production “Ramuan Sehat Jahe Merah” assisted by Mrs. Dian which moves on a home industry scale by empowering housewives. The business that was established for 2 years has experienced problems in product packaging and marketing. This product is only packaged into plastic bottles and lids with no airtight seal, so the product is prone to spillage during distribution, and this is often complained by buyers from another city. In addition, the absence of an airtight seal also makes customers doubt about the authenticity and durability of the product, this affects the level of product sales. In terms of marketing, this business has not carried out an intensive promotion, thus the marketing has not been maximized. Sales only occur when the buyer comes to the production house or orders the product via telephone. To resolve this problem, we provided assistance in the form of an induction sealer machine for product packaging and training in marketing. As a result, product sales increase, and the products integrity, durability and authenticity can be maintained.